Insight into the effect of organic and inorganic draw solutes on the flux stability and sludge characteristics in the osmotic membrane bioreactor - Siddique, MS; Khan, SJ; Shahzad, MA; Nawaz, MS; Hankins, NP (Elsevier, 2017)
In this study, chloride based (CaCl2 and MgCl2) and acetate based (NaOAc and MgOAc) salts in comparison with NaCl were investigated as draw solutions (DS) to evaluate their viability in the osmotic membrane bioreactor (OMBR). Membrane distillation was coupled with an OMBR setup to develop a hybrid OMBR-MD system, for the production of clean water and DS recovery. Results demonstrate that organic DS were able to mitigate the salinity buildup in the bioreactor as compared to inorganic salts. Prolonged filtration runs were observed with MgCl2 and MgOAc in contrast with other draw solutes at the same molar concentration. Significant membrane fouling was observed with NaOAc while rapid flux decline due to increased salinity build-up was witnessed with NaCl and CaCl2. Improved characteristics of mixed liquor in terms of sludge filterability, particle size, and biomass growth along with the degradation of soluble microbial products (SMP) were found with organic DS.